In situ UV-vis and EXAFS studies of ZnO quantum-sized nanocrystals and Zn-HDS formations from sol-gel route - Santilli, Celso Valentim [UNESP]; Pulcinelli, Sandra Helena [UNESP]; Tokumoto, M. S.; Briois, V. (Elsevier B.V., 2007)
We have pointed Out that. zinc-based particles obtained from zinc acetate sol-gel route is a mixture of quantum-sized ZnO nanoparticles, zinc acetate, and zinc hydroxide double salt (Zn-HDS). Aiming the knowledge of the mechanisms involved in the formation of ZnO and Zn-HDS phases, the thermohydrolysis of ethanolic zinc acetate solutions induced by lithium hydroxide ([LiOH]/[Zn2+] = 0.1) or water ([H2O]/[Zn2+] = 0.05) addition was investigated at different isothermal temperatures (40, 50, 60 and 70 degrees C) by in situ measurements of turbidity, UV-vis absorption spectra and extended X-ray absorption fine structures (EXAFS). Only the growth of ZnO nanoparticles was observed in sol prepared with LiOH, while a two-step process was observed in that prepared with water addition, leading the fast growth of Zn-HDS and the formation of ZnO nanoparticles at advanced stage. A mechanism of dissolution/reprecipitation governed by the water/ethanol proportion is proposed to account for relative amount of ZnO. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: sol-gel processing; spectroscopy; X-ray methods; ZnO